2019
DOI: 10.1155/2019/9796175
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Whole-Body Energy Homeostasis and Hepatic Energy Metabolism in Nondiabetic Humans with Fatty Liver

Abstract: Background. Fatty liver is believed to be sustained by a higher than normal adipose-derived NEFA flux to the liver. Also, hepatic energy metabolism may be a rate-limiting step of intrahepatic fat (IHF) accumulation. Aims. To assess whole-body energy metabolism and hepatic high-energy phosphates (HEPs) in individuals with fatty liver. Methods. We studied 22 individuals with fatty liver and 22 control individuals matched for anthropometric features by means of (1) hepatic 1H-magnetic resonance spectroscopy (MRS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…As to hepatic energy metabolism, limited availability of Pi for ATP synthesis can cause a decline of hepatic ATP concentrations 38 and HC nor with hepatic γATP and Pi levels suggesting that whole-body energy metabolism is not necessarily abnormal at least during early NAFLD development, in line with previous studies 39 .…”
Section: Changes In Hepatic Energy Metabolism In T2dm Over 5 Yearssupporting
confidence: 86%
“…As to hepatic energy metabolism, limited availability of Pi for ATP synthesis can cause a decline of hepatic ATP concentrations 38 and HC nor with hepatic γATP and Pi levels suggesting that whole-body energy metabolism is not necessarily abnormal at least during early NAFLD development, in line with previous studies 39 .…”
Section: Changes In Hepatic Energy Metabolism In T2dm Over 5 Yearssupporting
confidence: 86%
“…The exact mechanisms driving the rise in ALT levels during the early weeks of weight loss interventions are unclear and are beyond the scope of this study. It has previously been demonstrated that during fasting, increased adipose-derived non-esteri ed fatty acid (NEFA) ux to the liver occurs, promoting intra-hepatic fat accumulation [34][35][36]. Increased intrahepatic fat, in turn, has been associated with increased generation of fatty acids within the liver via de novo lipogenesis [37].…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanisms driving the rise in ALT levels during the early weeks of weight loss interventions are unclear and are beyond the scope of this study. It has previously been demonstrated that during fasting, increased adipose-derived non-esterified fatty acid (NEFA) flux to the liver occurs, promoting intra-hepatic fat accumulation [ 34 36 ]. Increased intrahepatic fat, in turn, has been associated with increased generation of fatty acids within the liver via de novo lipogenesis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Values are presented as Mean ± SD a Denotes variables that are not normally distributed presented as median [IQR] b Denotes variables that represent values higher than normal at the start of the programme c Denotes variables that represent values that were normal at the start of the programme The exact mechanisms driving the rise in ALT levels during the early weeks of weight loss interventions are unclear and are beyond the scope of this study. It has previously been demonstrated that during fasting, increased adipose-derived non-esterified fatty acid (NEFA) flux to the liver occurs, promoting intra-hepatic fat accumulation [34][35][36]. Increased intrahepatic fat, in turn, has been associated with increased generation of fatty acids within the liver via de novo lipogenesis [37].…”
Section: Table 2 Changes In Anthropometric and Metabolic Variables Ovmentioning
confidence: 99%